PEMANFAATAN TANAMAN Azolla pinnata UNTUK MENJAGA KUALITAS AIR PADA KOLAM PEMELIHARAAN IKAN PLATY PEDANG (Xiphophorus helleri) DI DESA KARANG BONGKOT, KECAMATAN LABUAPI, KABUPATEN LOMBOK BARAT - Diniariwisan, Damai; Batun Citra Rahmadani, Thoy; Sumsanto, Muhammad; Ayu Diamahesa, Wastu; Asri, Yuliana; Idris Affandi, Rangga; Abidin, Zaenal (Jurnal Pengabdian Perikanan Indonesia, 2022)
Karang Bongkot Village, is one of the villages in Labuapi District, West Lombok, where one of the economic sources of residents from the fisheries sector is ornamental fish cultivation. The obstacle often faced by cultivators is the condition of the water which is easily dirty due to the buildup of leftover feed and feces from fish. The purpose of this community service activity is to provide knowledge about the use of Azolla pinnata plants to maintain water quality in Platy Sword fish farming ponds. This activity was held on October 1, 2022 at the residence of Mr. Andik who is one of the Platy Sword fish cultivators. The method of implementing this activity includes direct practice accompanied by discussion. The result of the activity is the application of the use of Azolla plants as phytoremediation agents to maintain water quality in Platy Sword fish ponds. In addition, several other benefits of the Azolla plant itself were presented, such as a mixture of animal feed ingredients and the basic ingredients of natural fertilizers